PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH KABUPATEN KERINCI: IMAM ARDIAN, S.STP - IMAM ARDIAN (JURNAL ADMINISTRASI NUSANTARA, 2021)
This study aims to determine how much p engaruh leadership style, motivation of work, and discipline to employee performance BKPSDMD Kerinci, with a sample of 95 respondents employee BKPSDMD Kerinci district . The analytical method used is multiple regression analysis. The research results obtained based on partial test (t test) obtained: (a) partially there is a significant influence between leadership style on employee performance. Thus Ho is rejected and Ha is accepted. (b) partially significant effect between employee motivation t erhadap employee performance . Thus Ho is rejected and Ha is accepted. (c) partially significant effect between work discipline of work t erhadap employee performance . Thus Ho is rejected and Ha is accepted. (d) then based on the results of joint hypothesis testing (Test F) leadership style, work motivation, and work discipline positive and significant effect on employee performance. Based on the test of the coefficient of determination (R 2 ) obtained a value of 74.1%, this indicates that the percentage contribution of independent variables of leadership style, employee motivation, and discipline by 74.1% while the remaining 25.9% influenced by variables outside the research , such as employee commitment, organizational culture, training, and work environment. Finally, the authors suggest to the Kerinci Regency BKPSDMD to be able to increase work motivation and employee work discipline , leaders can implement a better leadership style and maintain a good leadership style .